Tomates y otras Verduras de Semilla: Practicas Seguras para Consumidores - Amy Simonne (EDIS)
FCS8738-Span, a 2-page factsheet by Amy Simonne, is the Spanish version of Tomatoes and other Seed-bearing Vegetables: Safe Handling Practices for Consumers (FCS8738). It gives guidelines and details on how to safely shop for and prepare seed-bearing vegetables, such as tomatoes and peppers. Published by the UF Department of Family, Youth, and Community Sciences, June 2007.